2021
DOI: 10.1038/s41598-021-01024-9
|View full text |Cite
|
Sign up to set email alerts
|

A priori prediction of local failure in brain metastasis after hypo-fractionated stereotactic radiotherapy using quantitative MRI and machine learning

Abstract: This study investigated the effectiveness of pre-treatment quantitative MRI and clinical features along with machine learning techniques to predict local failure in patients with brain metastasis treated with hypo-fractionated stereotactic radiation therapy (SRT). The predictive models were developed using the data from 100 patients (141 lesions) and evaluated on an independent test set with data from 20 patients (30 lesions). Quantitative MRI radiomic features were derived from the treatment-planning contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…They found that the addition of the top 10 radiomics features provided additional information regarding the standard routinely available clinical variables for predicting LF in BM following SRS. Similarly, Jaberipour et al ( 32 ) developed a predictive model using the pretreatment qMRI and clinical features of 100 patients, which was evaluated using an independent test set with data from 20 patients. All of the patients with BMs underwent SRT with a total dose of 22.5–35 Gy over 5 fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the addition of the top 10 radiomics features provided additional information regarding the standard routinely available clinical variables for predicting LF in BM following SRS. Similarly, Jaberipour et al ( 32 ) developed a predictive model using the pretreatment qMRI and clinical features of 100 patients, which was evaluated using an independent test set with data from 20 patients. All of the patients with BMs underwent SRT with a total dose of 22.5–35 Gy over 5 fractions.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of imaging and analysis technologies, qMRI biomarkers for predicting treatment response have gradually been acquired. Several studies (24,25) focused on the quantification of the peritumoral region before irradiation, while others (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) developed optimal quantitative prognostic models (with or without clinical data) by examining multiple geometrical and textural features of MR images pre-SRS with different sophisticated radiomics analysis frameworks to predict early treatment response. However, since the algorithms for image quantification were not standardized, the robustness and reproducibility of the relevant results were poor.…”
Section: The Relationship Between Anatomical/morphological Changes An...mentioning
confidence: 99%
“…Jiang et al saw no increase in AUC when using radiomic features alone compared to using radiomic and clinical features, though no baseline of using clinical features alone was established 15 . Studies on post-operative BM SRS or SRT found radiomic features outperformed clinical features and that clinical features decreased accuracy when combined with radiomic features 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…They investigated the use of radiomic features from multiple MRI sequences, the planned SRS dose distribution, and the peri-tumoural region beyond the treated BM [12][13][14][15][16] . There have also been similar studies for BM SRT and post-surgical resection SRS using Gamma Knife [17][18][19] .…”
mentioning
confidence: 82%
“…ML models have been established to predict response to stereotactic radiosurgery or radiation therapy in patients with brain metastasis (BM), specifically BM velocity, 71 local control, [72][73][74][75][76] and to classify true progression. 77,78 Two studies aimed to predict survival in patients with non-small-cell lung cancer and BM.…”
Section: Brain Metastasismentioning
confidence: 99%